2011
DOI: 10.1115/1.4005416
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopically Observed Deformations of a Compliant Abdominal Aortic Aneurysm Model

Abstract: A new experimental setup has been implemented to precisely measure the deformations of an entire model abdominal aortic aneurysm (AAA). This setup addresses a gap between the computational and experimental models of AAA that have aimed at improving the limited understanding of aneurysm development and rupture. The experimental validation of the deformations from computational approaches has been limited by a lack of consideration of the large and varied deformations that AAAs undergo in response to physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Digital image correlation has become widely used to measure displacements and strains of soft tissues, and a number of authors have calculated the accuracy and resolution of 3D-DIC displacements [37][38][39][40][41] and strains [40,42,43] using methods similar to those described here. For example, Sutton et al [42] reported a standard deviation of 0.03%-0.08% strain for a 3D translation of a cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…Digital image correlation has become widely used to measure displacements and strains of soft tissues, and a number of authors have calculated the accuracy and resolution of 3D-DIC displacements [37][38][39][40][41] and strains [40,42,43] using methods similar to those described here. For example, Sutton et al [42] reported a standard deviation of 0.03%-0.08% strain for a 3D translation of a cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…Then the "rubber aneurysm" can be pressure-loaded and its deformed configuration measured precisely, together with the surface strain field (e.g. by stereoscopic techniques (Meyer et al, 2011) or the photoelastic method (Doyle et al, 2012)). The load can be increased until the "rubber aneurysm" ruptures and the rupture site can then be located.…”
Section: Engineering Laboratory Vs a Typical Clinicmentioning
confidence: 99%
“…Abdominal Aortic Aneurysms (AAA) pose a serious health risk due to their potential for thrombus formation, dissection, and, more importantly, rupture [1,2]. In vitro studies on AAA have been performed since the end of the last century [3].…”
Section: Introductionmentioning
confidence: 99%